2013
DOI: 10.4081/ijas.2013.e2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Effects of Various Protein Levels with Constant Ratio of Digestible Sulfur Amino Acids and Threonine to Lysine on Performance, Egg Quality and Protein Retention in Two Strains of Laying Hens

Abstract: An experiment was conducted to determine the possibility of using various levels of crude protein (CP) by providing laying hens with constant levels of digestible sulfur amino acid, threonine and lysine to improve performance and egg quality. The experiment was conducted as a completely randomized block design in a factorial arrangement (4×2) with 8 replicates of 10 hens in each. Factors included 4 levels of CP (18.5%, 17.5%, 16.5% and 15.5%) and 2 strains (LSL and Hy-Line W-36) of laying hens. Hens were fed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
3
21
2
3
Order By: Relevance
“…In contrast to these, Mousavi et al (2013) observed linear increase in egg production (92.32 to 93.63%) with increase in crude protein (15.5 to 17.5%) in diet.…”
Section: Discussioncontrasting
confidence: 48%
“…In contrast to these, Mousavi et al (2013) observed linear increase in egg production (92.32 to 93.63%) with increase in crude protein (15.5 to 17.5%) in diet.…”
Section: Discussioncontrasting
confidence: 48%
“…Albumin height and egg weight have a direct and indirect contribution for the HU values, respectively in which the increase in albumin height increase the he HU and the increase in egg weight decrease HU. This is in line with the result demonstrated by Suk and Park (2001) that albumen weight is positively associated with egg weight and that of Mousavi et al (2013) who reported independence of HU and albumen height from dietary CP level. Wu et al (2007) Related HU to nutrients and stated that the HU of hens fed higher nutrient density was significantly lower than that of hens fed lower nutrient densities, probably because of the higher egg weight of hens fed the high nutrient density.…”
Section: Albumin Weight Height and Haugh Unitsupporting
confidence: 80%
“…Regarding the yolk relative weight, our results do not agree with Mousavi et al (2013), who investigated the effects of different levels of crude protein (15.5, 16.5, 17.5, and 18.5%) on the quality of the eggs of Lohmann LSL and Hy-Line W-36 lines between 25 and 33 weeks of age. These authors used diets formulated from the concept 35 weeks and 40 to 45 weeks of age) and reported that the yolk relative weight was higher for the breeding system in conventional cages.…”
Section: Discussioncontrasting
confidence: 55%